Introducing a sorting plant in the Kristineberg mine : an analysis of the effects on production - Skawina, Bartlomiej; Greberg, Jenny; Salama, Abubakary; Novikov, Evgeny (Luleå tekniska universitet, Geoteknologi, 2015)
This report is part of the work done by Luleå University of Technology within the EU 7th framework project I2Mine, Innovative Technologies and Concepts for the Sustainable and Intelligent Deep Mine of the Future. The work is performed within work package 2 Novel mining and underground processing methods, subtask 2.1.1 Novel mining methods and processes for deep, steeply dipping orebodies. Reaching the ore bodies that are located at greater depths require extensive transportation systems. The transported ore before being refined contains not only minerals that can be economically extracted from the production face but also waste. To reduce the amount of transporting unnecessary material up to the surface near to face sorting plant has been introduced. In this study near to face sorting plant was integrated in the simulation model that was based on one of the Boliden’s cut and fill mines for possible enhancement of the currentand future transportation systems to reduce the unnecessary amount of mass movement upstream. In this study discrete event simulation was used to study and analyse the mass movement before and after near to face sorter implementation. The paper shows the effects on the production rate and distribution of rock mass in the underground mine. When miningoperations will continue to reach greater depths, utilizing sorting technique would be advantageous, as it enables to leave the waste behind, hence reduces the costs necessary for transporting and processing unnecessary material further upstream. Taking into consideration the sorting plant speeds equal to or higher than 70 tph, the sorting plant was able to maintain the speed of the simulated production. If the sorting plant will maintain the speed at 30 tph during the simulation it was not possible to fulfil the yearly production blasting plan. In cases of necessary stockpiling of the material in front of the sorting plant, some of the material would have to bypass the sorting plant and be transported up via hoisting system with the rest of the ...